231k views
0 votes
(2x + y) (2x + 2y) =

User Icypy
by
4.8k points

2 Answers

9 votes

Answer:

4x² + 6xy + 2y²

Explanation:

Given

(2x + y)(2x + 2y)

Each term in the second factor is multiplied by each term in the first factor, that is

2x(2x + 2y) + y(2x + 2y) ← distribute both parenthesis

= 4x² + 4xy + 2xy + 2y² ← collect like terms

= 4x² + 6xy + 2y²

User Prototype
by
5.1k points
11 votes

Answer: 4x^2 + 6xy + 2y^2

Explanation:

(2x + y)(2x + 2y) =

2x*2x + 2x*2y + y*2x + y^2y =

4x^2 + 4xy + 2xy + 2y^2 =

4x^2 + 6xy + 2y^2

User TALlama
by
4.8k points